A Photoswitchable Ligand Targeting the β1‐Adrenoceptor Enables Light‐Control of the Cardiac Rhythm. Issue 30 (9th June 2022) - Duran‐Corbera, Anna; Faria, Melissa; Ma, Yuanyuan; Prats, Eva; Dias, André; Catena, Juanlo; Martinez, Karen L.; Raldua, Demetrio; Llebaria, Amadeu; Rovira, Xavier
Abstract: Catecholamine‐triggered β‐adrenoceptor (β‐AR) signaling is essential for the correct functioning of the heart. Although both β1 ‐ and β2 ‐AR subtypes are expressed in cardiomyocytes, drugs selectively targeting β1 ‐AR have proven this receptor as the main target for the therapeutic effects of beta blockers in the heart. Here, we report a new strategy for the light‐control of β1 ‐AR activation by means of photoswitchable drugs with a high level of β1 ‐/β2 ‐AR selectivity. All reported molecules allow for an efficient real‐time optical control of receptor function in vitro. Moreover, using confocal microscopy we demonstrate that the binding of our best hit, pAzo‐2, can be reversibly photocontrolled. Strikingly, pAzo‐2 also enables a dynamic cardiac rhythm management on living zebrafish larvae using light, thus highlighting the therapeutic and research potential of the developed photoswitches. Overall, this work provides the first proof of precise control of the therapeutic target β1 ‐AR in native environments using light. Abstract : New azobenzene‐based molecular photoswitches active for the therapeutic β1 ‐adrenoceptor (β1 ‐AR) are presented. The most promising candidate, named pAzo‐2, has a potency and β1 /β2 selectivity similar to approved beta blockers. Importantly, pAzo‐2 is compatible with imaging techniques and its potential as a cardioselective light‐controlled drug has been validated by the reversible photomodulation of the cardiac rhythm in living zebrafish larvae.